Synthesis and stability of bimetallic Au@Ag nanorods. (December 2016) - Wei, Jingjing; Kan, Caixia; Lou, Yeke; Ni, Yuan; Xu, Haiying; Wang, Changshun
Abstract: Bimetallic Au@Ag nanorods (NRs) with high purity have been synthesized via Ag overgrowth on the surface of as-obtained Au nanobipypramid (Au NBP). With the presence of different surfactants (CTAC, CTAB and BDAC), the growth mechanism of Au@AgNRs was proposed. It is found that the formation of Au@AgNRs is highly dependent on halogen ion (Cl- or Br-) of the surfactants. The Ag overgrowth rate in BDAC is less than that in CTAC, and the aspect ratios of Au@AgNRs prepared by BDAC are larger than that by CTAC. The optical properties show that the SPR of Au@AgNRs can be tuned in a large Vis-NIR spectral region. FDTD simulation was used to investigate the plasmon properties and localized field distribution of Ag@AuNR monomer, indicating that Ag@AuNRs possess a high SPR quality factor. Compared with AuNRs, the stability of Au@AgNRs was investigated under laser (λ = 980 nm) irradiation with different power. It is found that Au@AgNRs have high stability in shape and optical property, while AuNRs transform into particle and the SPR damp quickly. This research will provide an important reference for the fabrication of Au@AgNRs and further application.